Screening of genotypes against castor wilt (Fusarium oxysporum f.sp. ricini): SCREENING OF GENOTYPES AGAINST CASTOR WILT - K BHATI; R S BHAKTA; V A PATIL; V A LODAM (Journal of Oilseeds Research, 2018)
Assessment of genotypes by artificial wilt screening was done on a set of forty genotypes of castor grown during rabi 2015-16 at Pulses and Castor Research Station, Navsari Agricultural University, Navsari, Gujarat. Among the genotypes studied, 16 (JI-422,JI-384,JI-416,JI-402, JI-258, SKP-84, GEETA, JP-86, JI-368, JI-403, JI-423, JI-424, SKP-72, SKP-106, RG-43 and 48-1) showed resistant reaction for wilt disease. Thus the resistant genotypes can be used in breeding programme to develop wilt resistant varieties/hybrids in castor.